Roma - Hrvatić, Neven (1997)
Roma first came to Croatia in the 14th century. The first written document where Roma are mentiond dates back to 1373. from Dubrovnik (Monumenta Ragusina 1895). Two charasteristic forms of coexistence have led to the present position of Roma. In areas where they lived in relative isolation, in separate rural (or suburban) settelments, they have preserved their original ethnic identity, living in poverty and lagging behind their environment. Although in Croatia for more than six centuries, the Roma have not established their own national community. A higher level of political participation and better information services, as well as a better conceptualized education are indispensible if Roma are to be fully recognized in the Republic of Croatia.
Projekt MZOS
ENG